Guidelines for perioperative care in cataract surgery in Poland - Szaflik, Jacek P.; Bakunowicz-Łazarczyk, Alina; Dobrowolski, Dariusz; Grabska-Liberek, Iwona; Kałużny, Bartłomiej; Kałużny, Jakub; Lubiński, Wojciech; Mackiewicz, Jerzy; Michalska-Małecka, Katarzyna; Misiuk-Hojło, Marta; Mrukwa-Kominek, Ewa; Nowak, Agnieszka; et al. (Klinika Oczna / Acta Ophthalmologica Polonica, 2024)
The approach to cataract surgery procedures in Poland has changed significantly over the past few years. The authors outline the current principles of perioperative care in cataract surgery